The Foundation’s Commitment to Enhancing the Individual Well-Being of Integrated Islamic Junior High School Teachers in Jambi Province - Boby Yasman Purnama; Mukhtar Mukhtar; Wahyudi Wahyudi; M. Thontawi (Universitas Muhammadiyah Enrekang, 2024)
This research examines the commitment of foundations in enhancing the individual well-being of Integrated Islamic Junior High School (SMPIT) teachers in Jambi Province. The study explores multifaceted strategies, including financial stability, professional growth opportunities, and socio-cultural support, aimed at improving the quality of life and job satisfaction for teachers. Drawing upon Herzberg's Two-Factor Theory and Maslow's Hierarchy of Needs, the research emphasizes the importance of addressing both intrinsic and extrinsic factors in fostering teacher well-being. The findings reveal that a comprehensive and collaborative approach by foundations significantly impacts teacher motivation and performance, contributing to the sustainability of education development in Islamic schools. The study provides practical insights and recommendations for policymakers and educational stakeholders to further enhance teacher welfare systems.